2014
DOI: 10.9734/ijpss/2014/10367
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Regeneration Status of Trees Used in Making Wooden Mortar and Pestle in the Takamanda Rainforest South West Region, Cameroon

Abstract: Forest situated at the vicinity of communities hardly attained a fixed climax community over long period due to anthropogenic and natural factors. We investigated the density, population structure and regeneration status of six tree species (Annickia chlorantha, Baphia nitida, Irvingia gabonensis, Pterocarpus soyauxii, Terminalia ivorensis and Melicia excelsa) harvested for making of wooden mortars and pestles in three forest dependent communities. Data were collected through survey and focus group discussions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…This could be due to the fact that those that were married had an urge in NTFPs production and marketing as compared to those that were singled. This finding is in agreement with [35], who reported that both married and unmarried are involved in the collection of NTFPs as noticed in snail searching in the night were family took up torch lights in search for snails.…”
Section: Socio Demographic Characteristics Of Ntfps Respondentssupporting
confidence: 92%
“…This could be due to the fact that those that were married had an urge in NTFPs production and marketing as compared to those that were singled. This finding is in agreement with [35], who reported that both married and unmarried are involved in the collection of NTFPs as noticed in snail searching in the night were family took up torch lights in search for snails.…”
Section: Socio Demographic Characteristics Of Ntfps Respondentssupporting
confidence: 92%
“…Such medicinal plant species diversity depicts the contribution of medicinal plants as well as the traditional health knowledge held by the Mbo ethnic group in assisting the primary health care needs of the people of Nlonako. Similar indigenous ethnomedicinal knowledge were reported in different other parts of Cameroon, including the 30 medicinal plant species from Lewoh-lebang village in the South West region (Fonge et al, 2012) [27] , 39 medicinal plant species among communities of Takamanda in the South West region (Ndah et al, 2013) [66] . The similar number of medicinal plants may be due to the fact that, Mount Nlonako is in the same montane forest ecological zone.…”
Section: Ethnobotanic Characteristics Of the Mount Nlonako Forest Use...mentioning
confidence: 54%
“…This is so because in a large family, there is easy transfer of knowledge of plant used for traditional medicine since they live in the same home. [21,27,66,67] . The average level of education amongst farmers enables them to solve intricacies or difficulties related to production (agriculture).…”
Section: Plants Species Used For Cultural Purposesmentioning
confidence: 99%
“…The knowledge on the floristic compositions of plant community is a prerequisite to understand the overall structure and functioning of an ecosystem. However, regular human interventions like overgrazing, timber exploitation, non-timber forest products collection (NTFPS) and encroachments of forest areas (settlement, agriculture) are among the key regulatory factors controlling the distribution of plant species [19]. Furthermore, altitude is also one of the most important factors which determine the distribution of tree species due to its direct effect on the microclimatic conditions of the habitat [20].…”
Section: Discussionmentioning
confidence: 99%